2004
DOI: 10.1523/jneurosci.4426-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Locus Ceruleus Activation Initiates Delayed Synaptic Potentiation of Perforant Path Input to the Dentate Gyrus in Awake Rats: A Novel β-Adrenergic- and Protein Synthesis-Dependent Mammalian Plasticity Mechanism

Abstract: Norepinephrine, acting through ␤-adrenergic receptors, is implicated in mammalian memory. In in vitro and in vivo studies, norepinephrine produces potentiation of the perforant path-dentate gyrus evoked potential; however, the duration and dynamics of norepinephrine-induced potentiation have not been explored over extended time periods. To characterize the long-term effects of norepinephrine on granule cell plasticity, the present study uses glutamatergic activation of the locus ceruleus (LC) to induce release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
74
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 58 publications
(60 reference statements)
4
74
0
Order By: Relevance
“…Through combined application of b-adrenergic and muscarinic receptor agonists, LTP induced by low-frequency stimulation (5 Hz, 5 sec) was significantly enhanced relative to slices treated with stimulation alone, or stimulation paired with either agonist alone. The functional importance of this form of LTP is demonstrated by a requirement for translation which links this form of LTP to evidence implicating protein synthesis-dependent LTP in long-term memory formation (Abel et al 1997;Straube et al 2003;Walling and Harley 2004;Herrera-Morales et al 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Through combined application of b-adrenergic and muscarinic receptor agonists, LTP induced by low-frequency stimulation (5 Hz, 5 sec) was significantly enhanced relative to slices treated with stimulation alone, or stimulation paired with either agonist alone. The functional importance of this form of LTP is demonstrated by a requirement for translation which links this form of LTP to evidence implicating protein synthesis-dependent LTP in long-term memory formation (Abel et al 1997;Straube et al 2003;Walling and Harley 2004;Herrera-Morales et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Noradrenaline activates a-and b-adrenergic receptors which can, likewise, elicit opposing effects on cell excitability and synaptic plasticity (Gelinas et al 2008;Lemon et al 2009). Activation of either muscarinic (Shinoe et al 2005;Li et al 2007;Poulin et al 2010) or b-adrenergic receptors (Thomas et al 1996;Walling and Harley 2004;Gelinas and Nguyen 2005;Lemon et al 2009) can enhance synaptic strength and memory formation.…”
mentioning
confidence: 99%
“…A new study in our laboratory has shown that glutamatergic activation of the LC in awake rats produces a delayed ␤-adrenergic receptor-dependent facilitation of both the EPSP slope and population spike amplitude 24 hr after the LC glutamate infusion, an effect that does not require short-term facilitation (Walling and Harley, 2004). Whether orexinergic activation of LC neurons can initiate a similar pattern of synaptic strength changes at 24 hr remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…These effects of NA on plasticity in vivo are also mediated by ␤1-adrenoceptors and are probably related to the induction of LTP. Indeed, a recent study in awake rats found that LC stimulation was followed, 24 h later, by protein synthesis-dependent synaptic potentiation in the dentate gyrus (Walling and Harley, 2004). Finally, NA depletion prevents the expression during wakefulness of genes linked to the induction/maintenance of LTP [references in ].…”
Section: Discussionmentioning
confidence: 99%